Bioprospektif Perairan Berdasarkan Produktivitas : Studi Kasus Estuari Sungai Serayu Cilacap, Indonesia - Nur Laila Rahayu; W. Lestari; Erwin Riyanto Ardli (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
The high changes of Serayu River land use is resulting the high of load particle sedimentation into the body of water. Turbidity will accumulate in the downstream or estuaries which would have an impact on biota, especially plankton as primary productivity and secondary productivity. This research is conducted with a survey method and purposive sampling technique. Estuary Serayu River is divided into 5 stations, starts from the nearest to the sea (1) with 26 ‰ salinity and the furthest stations from the sea (5) with 8 ‰ salinity. Samples of water and plankton are taken at the time of high tide and low tide every month, for 4 months (August, September, October, and November 2016). The obtained data is analyzed by PCA to study the environmental factors towards primary productivity and secondary productivity. Based on the research result environmental factors has relation waters estuary productivity of Serayu river on the highest and lowest tide those are lightness, level TSS and pH.